Isolation and purification of six iridoid glycosides from gardenia jasminoides fruit by medium‐pressure liquid chromatography combined with macroporous resin chromatography. Issue 23 (12th November 2015) - Wang, Yun; Liu, Hui; Shen, Lifeng; Yao, Lan; Ma, Yinlian; Yu, Dingrong; Chen, Jianhong; Li, Puling; Chen, Ying; Zhang, Cun
Abstract : Gardeniae fructus is one of the most frequently used herbs in traditional Chinese medicine. In the present study, a process for the enrichment of six iridoid glycosides from Gardeniae fructus was developed using medium‐pressure liquid chromatography combined with macroporous resin and reversed‐phase chromatography. The purities of different fractions from Gardeniae fructus were assessed using quantitative high‐performance liquid chromatography. After fractionation using HPD‐100 column chromatography, a 30% ethanol fraction was selected based on high‐performance liquid chromatography and liquid chromatography with mass spectrometry qualitative analysis to separate and purify. Based on the orientation analysis results, six compounds—deacetyl asperulosidic acid methyl ester, gardenoside, ixoroside, scandoside methyl ester, genipin‐1‐ O ‐β‐d‐ gentiobioside, and geniposide—were successfully isolated and purified in three to four combined steps from Gardeniae fructus . The purities of these compounds were found by high‐performance liquid chromatography analysis to be 97.9, 98.1, 95.5, 96.3, 97.1, and 98.7%, respectively. Moreover, their structures were elucidated by NMR spectroscopy and liquid chromatography with tandem mass spectrometry. The separation process was highly efficient, rapid, and accurate, making it a potential approach for the large‐scale production of iridoids in the laboratory and providing several marker compounds for quality control. This procedure may be meaningful for the purification of other natural products used in traditional Chinese medicine.